A mouse model to study thrombotic complications of thalassemia. Issue 3 (March 2015) - Kalish, Yosef; Malyutin, Zeev; Shai, Ela; Dana, Mutaz; Avraham, Limor; Jahshan, Nivin; Rachmilewitz, Eliezer; Fibach, Eitan; Varon, David
Abstract Patients with β-thalassemia major and mainly intermedia have an increased risk for developing venous and arterial thrombosis which may be related to circulating pathological red blood cells (RBC) and continuous platelet activation. In the present study we used a modified thalassemic mice model in conjunction with a "real-time" carotid thrombus formation procedure to investigate thrombotic complications of thalassemia. Heterozygous Th3/+ mice, which lack one copy of their β-major and β-minor globin genes, exhibit anomalies in RBC size and shape, chronic anemia and splenomegaly which recapitulate the phenotype of human β-thalassemia intermedia. Flow cytometry measurements showed higher reactive oxygen species generation, indicating oxidative stress, in platelets and RBC of the thalassemic mice compared with wild type mice concomitant with an increase in reduced glutathione content which may represent a compensatory response to oxidative stress, and exposed phosphatidylserine which indicates platelet activation. To elucidate the effect of thalassemia on the development of arterial thrombosis, we studied photochemical-induced real-time thrombus formation in the carotid artery of these mice. The results indicated a significantly shorter "time to occlusion" in the thalassemic mice compared to wild type mice, which was prolonged following in vivo aspirin treatment. We suggest that this mouse model may contribute to our understanding of platelet activation and the hypercoagulable state in thalassemia and lay foundations to screening of anti-platelet drugs as well as anti-oxidants as possible therapeutics for prevention of thrombosis in thalassemia patients.